Avaliação do uso de coagulante orgânico TANFLOC para remoção de contaminante emergente Ibuprofeno - Silva, Vitoria Carolina da (2025)
The global water resource crisis impacts billions of people, exacerbating water scarcity and quality issues. In Brazil, challenges include pollution and lack of sanitation. Water treatment relies on chemical coagulants, but sustainable alternatives, such as tannins, show promise. Additionally, emerging contaminants, such as pharmaceuticals, are not regulated in the country and may pose environmental and health risks. Considering this, this study aimed to evaluate the applicability of the organic coagulant Tanfloc in treating synthetic water contaminated with Ibuprofen. To achieve this, an Ibuprofen calibration curve was developed, followed by the preparation and characterization of the raw sample and the coagulant. Turbidity and apparent color were determined, along with the sample's absorbance. Subsequently, coagulation, flocculation, and sedimentation tests were conducted using the Jar-test, varying the coagulant concentration and sedimentation time. After treatment, the samples were analyzed to assess contaminant removal and its impact on turbidity and apparent color parameters. There was a reduction in turbidity, especially in tests using lower coagulant concentrations and sedimentation times. However, there was an increase in apparent color, mainly in samples with higher coagulant concentrations. The highest average Ibuprofen removal efficiency was 70%, achieved with the highest coagulant concentration and the shortest sedimentation time, while the lowest was 40%, using an intermediate coagulant dosage and a longer sedimentation time. Considering the zeta potential, the most suitable coagulant dosages for promoting colloidal dispersion were 14 mg/L and 18 mg/L. Tests with larger particles were not the most efficient, possibly due to particle instability. Conversely, tests with smaller particles showed similar removal efficiency and greater particle stability, suggesting better performance in colloidal dispersion. Therefore, the study achieved satisfactory treatment efficiency, demonstrating the usability of Tanfloc for this type of treatment.